Case report: Efgartigimod is a novel therapeutic option for ocular myasthenia gravis: a report of 2 cases - Ma, Tianying; Zhu, Ying; Zhu, Ruixia (Frontiers in Immunology, 2025)
IntroductionEfgartigimod has been approved for the treatment of acetylcholine receptor antibodies-positive generalized myasthenia gravis (AChR-Ab+gMG), but its efficacy in patients with ocular myasthenia gravis (OMG) is not known.Case presentationWe describe 2 cases of patients with AChR-Ab+ OMG who showed unfavorable responses to corticosteroids and tacrolimus. Within 2 weeks of initiating efgartigimod, both patients showed rapid improvement and minimal symptom expression was achieved in weeks 3 to 4, which was maintained up to week 12.ConclusionThe 2 cases described herein provide preliminary evidence for the effectiveness of efgartigimod for the treatment of OMG for patients who do not respond or are intolerant to conventional medications. Large-scale studies are needed to confirm these findings.